ACUTE AND SUBLETHAL TOXICITY TEST OF LAUNDRY WASTES ‎TO Oreochromis niloticus - Diana Novita; Saberina Hasibuan; Syafriadiman Syafriadiman (Berkala Perikanan Terubuk, 2020)
This research was conducted on July 1, 2019 until Agustus 8, 2019 at the Laboratory of Environmental Quality of Culture, Faculty of Fisheries and Marine, University of Riau. Objective of this study to determine the effect of laundry liquid waste on the acute toxicity test and sub lethal of Oreochromis niloticus and safe doses for the growth of O. niloticus. Determination of 96-h LC50 using the EPA probit method by using a statistical formed through the data of mortality (mortality) of test fish and the length of exposure time was briefly carried out withsoftware Probit Analysis in the SPSS program. In acute toxicity the value obtained of 96-h LC50 is 512,23 ml/ L and ‎the safe biological value (Biological Safety Level) is  5,12 ml/L.‎ In the sublethal test the best treatment during the study was found in treatment P1 (5,12 ml/L) with absolute weight growth of 1,28 g, specific growth rate of 1,37% and survival of  90%.